STRATEGI PENGEMBANGAN EKOWISATA MELALUI KONSEP COMMUNITY BASED TOURISM (CBT) DALAM UPAYA MENINGKATKAN PEREKONOMIAN MASYARAKAT (STUDI KASUS: DESA PENDEM, KECAMATAN MOJOGEDANG) - Candrawati Putri Purnomo; Setya Nugraha; Gentur Adi Tjahjono (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2024)
Pendem Village is one of the villages in Mojogedang District, Karangnyar Regency which is rich in potential natural resources that can be used as tourist areas Ecotourism is one of the activities in sustainable tourism that utilizes tourism activities to develop environmental conservation through education and changes in community behavior. The research method used in this study is a quantitative method with a descriptive approach. The data collection used in this study was field observation and interviews. The results in the study show the level of land suitability of all ecotourism objects in Pendem Village is included in the Quite Suitable (S2) class. The community-based ecotourism potential assessment in Pendem Village is divided into 2 classes, namely Sendang Bulu is included in the Very Potential class while Toya Wening, Jamu Education, Biogas Education and Bukit Penthuk are included in the potential class. The community-based ecotourism development strategy using SWOT analysis of 5 ecotourism objects obtained by S-T (Strengths-Threats) is suitable to be applied to Sendang Bulu and Toya Wening Objects, because both objects are potential objects but require efforts by diversifying strategies in facing future challenges. The S-O (Strength-Opportunities) strategy is suitable to be applied to the objects of Herbal Medicine Education and Biogas Education. While the other object, Penthuk Hill, is suitable to apply the W-O (Weaknesses-Opportunities) strategy, because the object is lacking in terms of facilities and infrastructure such as improving road conditions.